A new model for the terminal settling velocity of microplastics. (March 2022) - Yu, Zijian; Yang, Ge; Zhang, Wenming
Abstract: Microplastic (MP) settling process is important for the transport of microplastic particles (MPs, <5 mm) in water bodies. However, for the control parameter of the drag coefficient ( C d ), no generalized formula has been proposed for MPs of different shapes and materials. In this study, a total of 1343 MP settling data were collected from the literature. It was found that the drag law for perfect spheres cannot reasonably predict C d for MPs with particle Reynolds number of 1–10 3 . A new formula for C d was developed by introducing the dimensionless particle diameter ( d ⁎ ) and two shape descriptors. The absolute error of the new formula is 15.2%, smaller than those (42.5–72.8%) of other existing formulas. Moreover, an explicit model was developed for MP settling velocity by correlating C d, d ⁎, and shape descriptors, with lower absolute error (8.8%) than those (15.4–77.2%) of existing models. Graphical abstract: Unlabelled Image Highlights: Spherical drag laws greatly underestimate C d for MPs in the transitional regime. MP shapes have a great impact on C d ; CSF and Ф can fully describe the shape effects. The new model can more accurately predict C d and terminal settling velocity of MPs.